Dual c‐Jun N‐terminal kinase–cyclin D1 and extracellular signal‐related kinase–c‐Jun disjunction in human melanoma. (1st December 2016) - Pathria, G.; Garg, B.; Garg, K.; Wagner, C.; Wagner, S.N.
Summary: Background: Activity of both c‐Jun and cyclin D1 is deemed critical for melanoma cell proliferation. This functionality is corroborated by frequently elevated expression and activity of these proteins in human melanomas. Correspondingly, alleviating c‐Jun and cyclin D1 function is vital to the success of antimelanoma therapeutics. Objectives: To understand the role of the c‐Jun N ‐terminal kinase (JNK) signalling pathway in melanoma cell proliferation and survival. Methods: The effect of JNK inhibitors SP600125 and JNK‐IN‐8 on the proliferation and survival of genetically highly representative human melanoma cell lines was studied in assays of proliferation and apoptosis. Changes in c‐Jun and cyclin D1 protein and mRNA levels in response to JNK and mitogen‐activated protein kinase kinase (MEK) inhibition were investigated through immunoblotting and quantitative reverse‐transcription polymerase chain reaction. The effects of JNK and MEK inhibitors on cell‐cycle distribution were assessed by flow cytometry. Results: We demonstrate the requirement of JNK signalling in melanoma cell proliferation and survival. While JNK inhibition suppressed the expression and activity of c‐Jun, it failed to suppress cyclin D1 levels. Consistently with its inability to downregulate cyclin D1, JNK inhibition failed to induce G1 arrest. In contrast, the blockade of MEK–extracellular signal‐regulated kinase (ERK) signalling, although unable to suppress c‐Jun activity and expression, paradoxically abated cyclin D1 levels and triggered G1 arrest. This previously unreported dual disconnect between JNK–cyclin D1 and ERK–c‐Jun levels was confirmed by concomitant JNK and BRAF inhibition, which suppressed both c‐Jun and cyclin D1 levels and exhibited a heightened antiproliferative response. Conclusions: Dual disjunction between JNK–cyclin D1 and ERK–c‐Jun signalling forms the basis for further investigation of combined JNK and MAPK signalling blockade as a more effective therapeutic approach in human melanoma.